The Dose-Dependent Effects of Vascular Risk Factors on Dynamic Compensatory Neural Processes in Mild Cognitive Impairment - Chen, Haifeng; Su, Fan; Ye, Qing; Wang, Zan; Shu, Hao; Bai, Feng (Frontiers in Aging Neuroscience, 2018)
Background/Objectives: Mild cognitive impairment (MCI) has been associated with risk for Alzheimer's Disease (AD). Previous investigations have suggested that vascular risk factors (VRFs) were associated with cognitive decline and AD pathogenesis, and the intervention of VRFs may be a possible way to prevent dementia. However, in MCI, little is known about the potential impacts of VRFs on neural networks and their neural substrates, which may be a neuroimaging biomarker of the disease progression. Methods: 128 elderly Han Chinese participants (67 MCI subjects and 61 matched normal elderly) with or without VRFs (hypertension, diabetes mellitus, hypercholesterolemia, smoking and alcohol drinking) underwent the resting-state functional magnetic resonance imaging (fMRI) and neuropsychological tests. We obtained the default mode network (DMN) to identify alterations in MCI with the varying number of the VRF and analyzed the significant correlation with behavioral performance. Results: The effects of VRF on the DMN were primarily in bilateral dorsolateral prefrontal cortex (DLPFC) (i.e., middle frontal gyrus). Normal elderly showed the gradually increased functional activity of DLPFC, while a fluctuant activation of DLPFC was displayed in MCI with the growing number of the VRF. Interestingly, the left DLPFC further displayed significantly dynamic correlation with executive function as the variation of VRF loading. Initial level of compensation was observed in normal aging and none-vascular risk factor (NVRF) MCI, while these compensatory neural processes were suppressed in One-VRF MCI and were subsequently re-aroused in Over-One-VRF MCI. Conclusions: These findings suggested that the dose-dependent effects of VRF on DLPFC were highlighted in MCI, and the dynamic compensatory neural processes that fluctuated along with variations of VRF loading could be key role in the progression of MCI.